(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
The essence of national and universal values, as well as their influence on strengthening the family institution and intergenerational relations, is axiomatic. Humanity has entered such a stage of historical development that no nation, people, or state can progress without engaging in broad integration with others, contributing to global development, participating in solving global problems, and benefiting from universal norms, achievements, and values.